تعليم خط النسخ العربي باستخدام طريقة العرض التوضيحي لتحسين كتابة القرآن الكريم في معهد سنان أمبيل العالي جامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج - Muhammad Farih (Journal of Calligraphy, 2023)
Teaching Arabic calligraphy to write the Noble Qur’an among middle class students in the Holy Qur’an education program from one of the educational programs at the sunan Ampel Higher Institute, Maulana Malik Ebrahim State Islamic University Malang in 2022. Teaching Arabic calligraphy can have a great impact on writing the Noble Qur’an. The Arabic Naskh script is taught using the display method and its effect to improve the writing of the Noble Qur’an among students of the middle class E in the Holy Quran Teaching Program at the sunan ampel Higher Institute, Maulana Malik Ibrahim State Islamic University Malang in 2022. To obtain these results, the researcher searches Classroom Action or procedural research uses The teacher is a researcher, so he is responsible for the research. The results of the first round show the maximum results, the data partly an increase in education results from the first encounter data to the second by 4.00 points from the lowest score from 68.2857143 to 72.2857143 However, after cumulative analysis of the average value of the first session from the first encounter and the second, the two highest score 77, and the lowest Score 59, average class value 70.5789474, KKM 65 achievement with a maximum of 27 people (77%) of the total student population up to 35 people, KKM 65 achievement with a minimum of 8 people (23%), and in the second round with 5.00 points of average class value 75.83 to 82.8. While the results of the cumulative analysis of the average value of the second session from the third and fourth meetings, the highest score was 88, the lowest score was 72.5, the average class value was 79.3142857, and the achievement of KKM 65 up to 35 people (100%) out of a total of 35 students. These data show that the research success indicators have been achieved (well's teaching) and will be consistent with the previously defined learning success indicators.